PENGGUNAAN GEOGEBRA DALAM PENGEMBANGAN PEMBELAJARAN INTERAKTIF MATA PELAJARAN MATEMATIKA SMA - Hedi; Sri Nur Yuliyawati (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
Mathematics learning is often complained of by most high school teachers because it is not able to attract students' interest. This can be overcome by applying mathematical software so that it has a positive impact and increases student interest in learning. For this reason, Community Service Activities are carried out in the form of "Interactive Learning for High School Mathematics Using GeoGebra" for MGMP Mathematics at SMA Negeri Cimahi. The purpose of this is to increase the knowledge and skills training of SMA Cimahi teachers in delivering mathematics subject matter using GeoGebra. This training was attended by 30 teachers who are members of the Mathematics MGMP of SMA Cimahi. The training is carried out face-to-face in several Cimahi Public High Schools alternately for 40 hours with a duration of five weeks. The results of this training show the topic "Algebraic Equations and Graphs of Functions", all participants are very familiar with the use of Geogebra. On the topic of “Integral”, almost all participants are very good at using Geogebra and only a few participants are less proficient. On the topic “Boundary Concepts. Concept of Derivation, Concept of Rieman's Sum, and Transformation, most of the participants were very mastered, there were some participants who mastered it and only a small part who still lacked it. Thus, this training has increased the competence of the trainee mathematics teachers in operating the GeoGebra software in learning mathematics. This really supports them in learning mathematics in the class they teach so that their students are enthusiastic.